(untitled) (Orthodontic Journal of Nepal, 2018)
Introduction: obesity has become an alarming concern worldwide. Obesity is not only a cosmetic concern, it is a health risk that threatens an individual’s wellness. As the prevalence of obesity increases so have the related health consequences. Objective: To determine the association of obesity with periodontal disease using Body Mass Index (BMI) Asian version, Oral Hygiene Index (OHI) and Community Periodontal Index (CPI) to assess the periodontal health and oral hygiene. Materials & Method: Body Mass Index was determined for 300 patients visiting the Department of Periodontics. The oral hygiene status was assessed by using Oral Hygiene Index Simplified-1964. The Community Periodontal Index was used to assess the periodontal status with a CPITN probe. The demographic details were collected using open ended questionnaire which included age, sex, socioeconomic status, education whereas smoking and stress were included in the close ended questionnaire. Result: The present study showed association of obesity with periodontitis. Males had higher prevalence of periodontitis. Similarly age and smoking also had a higher prevalence rate of periodontitis. Conclusion: As an oral health care professional, preserving periodontal health is the utmost responsibility. Finding and controlling new risk indicators and eliminating them is one of the most important relevance of the present study. Obesity has been identified as one more risk indicator other than age, smoking and diabetes mellitus